A Scoping Review to Identify Barriers and Enabling Factors for Nurse-Patient Discussions on Sexuality and Sexual Health - Maria Åling; Agnes Lindgren; Hillevi Löfall; Leah Okenwa-Emegwa (MDPI AG, 2021)
Background: Sexuality and sexual health (SSH) are essential aspects of care that have evolved since a 1975 World Health Organization (WHO) report on SSH. However, nurses still consider discussing the subject with patients a challenge. This scoping review aimed to map, synthesize, and summarize findings from existing literature regarding barriers and enabling factors for nurse-patient SSH discussions in care contexts. Methods: A scoping review model inspired by Arksey and O'Malley was used to search for and synthesize studies published between 2009 and 2019. The databases searched were the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Medical Literature Analysis and Retrieval System Online, i.e., MEDLARS Online. A total of nineteen articles were eligible to be included. Results: Two main categories of enabling factors were identified, i.e., a professional approach via using core care values and availability of resources. Three major categories of barriers were identified: beliefs and attitudes related to age, gender, and sexual identity; fear and individual convictions; and work-related factors. Conclusions: Applying professionalism and core care values as well as making resources available are likely to promote SSH discussions between nurses and patients. Moreover, there is a need for a norm-critical approach in education and practice.